Mathematical Software For Evaluating And Supporting The Selection Decision On Academic Programs; Advances in Computer Science Research; Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016) - Zakharova A. A. Aleksandra Aleksandrovna (2016, 2016)
Title screen